Impact of Specific N-Glycan Modifications on the Use of Plant-Produced SARS-CoV-2 Antigens in Serological Assays - Schwestka, Jennifer; König-Beihammer, Julia; Shin, Yun-Ji; Vavra, Ulrike; Kienzl, Nikolaus F.; Grünwald-Gruber, Clemens; Maresch, Daniel; Klausberger, Miriam; Laurent, Elisabeth; Stadler, Maria; Manhart, Gabriele; Huber, Jasmin; et al. (Frontiers in Plant Science, 2021)
The receptor binding domain (RBD) of the SARS-CoV-2 spike protein plays a key role in the virus-host cell interaction, and viral infection. The RBD is a major target for neutralizing antibodies, whilst recombinant RBD is commonly used as an antigen in serological assays. Such assays are essential tools to gain control over the pandemic and detect the extent and durability of an immune response in infected or vaccinated populations. Transient expression in plants can contribute to the fast production of viral antigens, which are required by industry in high amounts. Whilst plant-produced RBDs are glycosylated, N-glycan modifications in plants differ from humans. This can give rise to the formation of carbohydrate epitopes that can be recognized by anti-carbohydrate antibodies present in human sera. For the performance of serological tests using plant-produced recombinant viral antigens, such cross-reactive carbohydrate determinants (CCDs) could result in false positives. Here, we transiently expressed an RBD variant in wild-type and glycoengineered Nicotiana benthamiana leaves and characterized the impact of different plant-specific N-glycans on RBD reactivity in serological assays. While the overall performance of the different RBD glycoforms was comparable to each other and to a human cell line produced RBD, there was a higher tendency towards false positive results with sera containing allergy-related CCD-antibodies when an RBD carrying 1,2-xylose and core 1,3-fucose was used. These rare events could be further minimized by pre-incubating sera from allergic individuals with a CCD-inhibitor. Thereby, false positive signals obtained from anti-CCD antibodies, could be reduced by 90%, on average